Politics at the centre the selection and removal of party leaders in the Anglo parliamentary democracies - Cross, William P. (William Paul), 1962-; d; European Consortium for Political Research (Oxford : Oxford University Press, 2012)
'Politics at the Centre' studies the ways in which political parties select and remove their leaders in five parliamentary democracies: Australia, Canada, Ireland, New Zealand and the United Kingdom. It addresses the subject through cross-national comparison of 25 parties in these countries from 1965 to the present day.
At foot of title: ecpr.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Political parties -- Cross-cultural studies; Political leadership -- Cross-cultural studies; Cabinet system -- Cross-cultural studies; Elections -- Cross-cultural studies